The Elements Characterization of Conversion Low-Rank Coal through Carbonization Step to Activated Carbon - Alwathan Sofian; Siti Hamidah Mohd-Setapar; Muh. Irwan; Ramli Thahir; Dedi Irawan (Chemical Engineering Transactions, 2023)
East Kalimantan is a province that has the largest coal reserves in Indonesia. One type of coal that is widespread and has low economic value as an energy source is low-rank coal. Low rank coal is a type of coal that has a low calorific value, that is, the calorific value of low rank coal is in the range of the lowest to the highest value, from 3000 cal – 5000 cal. One way to increase the added value of low-rank coal is to convert the coal into activated carbon which can act as an adsorbent medium, this can be done because low-rank coal also has a carbon content of around 30 % W. element in the conversion stage of low-rank coal into activated carbon coal, besides that, we want to know its ability as an adsorbent medium based on the adsorption of the iodine number. The activation process is carried out through the carbonization step which is carried out at a temperature of 600 °C for 3 h and then followed by chemical-physical activation of the carbonized material soaked with chemicals (H3PO4 + Na2HCO3) 2.5 M for 8 h and physically activated at a temperature of 800 °C for 1.5 h. The results obtained were an increase in carbon content and adsorption capacity which respectively reached 73.79 % at carbon content and 1,163.513 mg/g at iodine adsorption number.